How interest groups shape industrial policy: the case of MENA countries - Kurdli, Susan Nashra (Nanyang Technological University, 2023)
How can we explain the varying levels of diversification-oriented industrialization in the Middle East and North Africa (MENA) in spite of the seemingly many similarities among countries of the region such as regime type, resource abundance, geography, history, culture, etc.? This doctoral dissertation argues that domestic political structures in resource-abundant countries play a crucial role in whether the country utilizes its natural-resource revenue for instant public consumption or for long-term investment. This research finds that states with the presence of stronger interest groups lobbying for their preferences through formal and informal channels are more likely to allocate resource rents to industrial plans that expand economic growth. The effect of interest groups on industrial diversification is amplified when a leader has a long-term horizon. This is primarily because a leader who expects long tenure needs to maximize growth beyond the export of volatile and exhaustive natural resources. Diversification-oriented industrialization is one of the key means to ensuring a long-term source of growth. Otherwise, the leader would have not invested in industrial projects that do not yield immediate payoff. Instead, they would have spent resource rents on their own members in the form of distributive policies, such as transfers, and direct subsidies. By examining three MENA countries, Libya, the UAE and Saudi Arabia, this research demonstrates that, counter intuitively, strong interest groups in resource-rich countries result in higher levels of diversification-oriented industrialization.